Target for 100% Renewable Energy Systems Use in Cyprus for Electricity Production - Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2020)
Cyprus covers 93% of the energy demand using fossil fuels which are fully covered from imports. This does not only stand as a barrier to the various European Directives and measures which apply for all EU members, but it is also a drawback for the economy of Cyprus. Around 1000 tons of heavy fuel oil is required every year by the Electricity Authority of Cyprus to cover the energy demand. The household electricity prices including taxes paid in Cyprus are the 7th highest in Europe. From 2009, renewable energy systems have started to be used, but due to the price of the systems they were limited. However, price was not the main problem of the systems to explain why they didn’t expand more. Many other parameters are still affecting the use of RES in Cyprus; the public acceptance, the education of people, the environmental consciousness, but the most important is the motivation and ease of the applications and licensing from the government parties. Here in this study, an overview of the current energy situation is discussed and suggestions to increase the use of RES are mentioned as well. These include the use of electricity production RES for the domestic needs and measures for the improvement of energy efficiency of the building sector in general, which is the second biggest energy consumer in Cyprus after the commercial sector.
Keywords: Renewable energy systems; 100% RES; Cyprus electricity production; Energy efficiency